2023
DOI: 10.1038/s41598-023-28829-0
|View full text |Cite
|
Sign up to set email alerts
|

Lemon grass essential oil improves Gladiolus grandiflorus postharvest life by modulating water relations, microbial growth, biochemical activity, and gene expression

Abstract: Gladiolus (Gladiolus grandiflorus Andrews) is a high-valued bulbous cut flower. However, the shorter postharvest life of the gladiolus, limits its marketing and commercial value. In the present investigation, the effect of lemon grass (LG) essential oil as an antimicrobial agent was studied towards increasing the vase life of gladiolus. The results revealed that as compared to control (distilled water), treatment with a lower concentration of 5 µL L−1 LG essential oil prolonged the vase life of gladiolus up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
3
3
0
Order By: Relevance
“…Unlike the control spikes, EO-treated ones exhibited a considerable reduction in their H 2 O 2 and MDA levels, which can be justified by the fact of considerable amounts of phenol and antioxidant compounds in the EOs that enable gladiolus florets to alleviate oxidative damage. These results are in agreement with previous reports of using lemongrass essential oil in gladioli [25] and ginger essential oil in Davallia solida [45]. The content of MDA was markedly decreased in gladiolus florets in response to the application of sage or rosemary EOs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Unlike the control spikes, EO-treated ones exhibited a considerable reduction in their H 2 O 2 and MDA levels, which can be justified by the fact of considerable amounts of phenol and antioxidant compounds in the EOs that enable gladiolus florets to alleviate oxidative damage. These results are in agreement with previous reports of using lemongrass essential oil in gladioli [25] and ginger essential oil in Davallia solida [45]. The content of MDA was markedly decreased in gladiolus florets in response to the application of sage or rosemary EOs.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings have been reported to extend the vase life of cut gladiolus spikes using natural leaf extracts rich in phenolic compounds [16]. Similarly, a positive role of various EOs in enhancing water relations and limiting bacterial growth has been reported in several plant species, such as using Shirazi thyme EO in gerbera [22], Salvia rosmarinus EO in carnations [23], Mentha piperita EO in gladioli [16], Mentha spicata EO in roses [24] and lemon grass EO in gladioli [25].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Additionally, nonenzymatic antioxidants such as anthocyanin constitute an endogenous defense against ROS in flower tissues, with anthocyanin also contributing to petal color [ 66 ]. Many studies on cut flowers have demonstrated that natural antioxidants, including essential oils [ 67 , 68 ], salicylic acid [ 69 ], and moringa extract [ 70 ], delay senescence and extend vase life by increasing ROS scavenging activity; this also helps the flower retain anthocyanin content. In peppermint essential oil, the most powerful free radical scavenging compounds are menthone and isomenthone [ [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%